2011
DOI: 10.1097/jnr.0b013e3182389e34
|View full text |Cite
|
Sign up to set email alerts
|

Taiwanese Fathers’ Experiences of Having Their Child Diagnosed With a Developmental Disability

Abstract: Fathers feel shock and despair as well as personally devalued when learning that their child has been diagnosed with a developmental disability. Chinese cultural beliefs and values can elicit different experiences for fathers while helping them make sense of their experiences and accept their child in meaningful ways. Nurses can actively engage fathers as well as mothers to understand their feelings and thoughts about their child's disability to provide appropriate emotional and informational support. Providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…The emotional downturn of loss, grief and shock is a finding congruent with other studies of fathers who had also been preparing for the birth of a typically developing child which did not come to fruition (Boström & Broberg, ; Fernandez‐Alcántara et al., ; Goff et al., ; Huang, St John, Tsai, & Chen, ; Takataya et al., ; Torquato et al., ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The emotional downturn of loss, grief and shock is a finding congruent with other studies of fathers who had also been preparing for the birth of a typically developing child which did not come to fruition (Boström & Broberg, ; Fernandez‐Alcántara et al., ; Goff et al., ; Huang, St John, Tsai, & Chen, ; Takataya et al., ; Torquato et al., ).…”
Section: Discussionsupporting
confidence: 80%
“…This Irish study extends the knowledge of fathers’ experiences within the context of leading up to the diagnosis and the actual diagnosis of a child’s intellectual disability. Regardless of the timing of the diagnosis, all fathers experienced an emotional downturn, a view supported throughout the literature (Bourke et al., ; Davys et al., ; Huang et al., ; Takataya et al., ; Waite‐Jones & Madill, ). While fathers are affected by the diagnosis of a child’s intellectual disability, healthcare professionals must recognise and respond to their distinct and individual needs at this critical diagnostic period.…”
Section: Discussionmentioning
confidence: 68%
“…This directness was also favoured by many Japanese fathers who received the diagnosis of Down syndrome following their child's birth (Takataya et al, 2016). For others, the provision of a diagnosis in later months or years by healthcare professionals was found to be at times, almost insensitive and blunt (Huang et al, 2011), a finding resonating across this and other studies in which parents were dissatisfied with healthcare professionals' disclosure of a child's disability (Close, Sadler, & Grey, 2016;Coons, Watson, Schinke, & Yantzi, 2016;Crane, Chester, Goddard, Henry, & Hill, 2016;Nelson Goff et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…Becoming a father is often life changing and a significant personal milestone (Gage & Kirk, 2016;Yarwood, 2011) in which a man's status changes from that of son, brother, uncle, partner or husband to that of father (Chin, Hall, & Daiches, 2011). The transition to fatherhood brings a mix of excitement and apprehension and for many is rewarding (Huang, St, Tsai, & Chen, 2011). Despite policy developments over the past 50 years, a meta-ethnographic analysis of 62 research studies found that fathers are not yet fully accepted and supported to fulfil parental roles (Wells, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant resources could also be useful for promoting the mental well-being of the caregivers. The critical period just before and after confirmation of the child's condition is when the parents often experience a high level of insecurity and anxiety due to the lack of relevant information and medical knowledge [14,15]. Parents given access to the relevant information would become less despondent as they would have a better understanding of this medical condition and could learn about strategies to overcome the types of obstacles that are likely to occur [16].…”
Section: Introductionmentioning
confidence: 99%